Biomechanical Evaluation of the Fatigue Performance, the Taper Corrosion and the Metal Ion Release of a Dual Taper Hip Prosthesis under Physiological Environmental Conditions. (December 2017) - Baxmann, M.; Pfaff, A.M.; Schilling, C.; Grupp, T.M.; Morlock, M.M.
Abstract: Besides numerous advantages of dual taper hip prosthesis such as the intraoperative flexibility and the improved reconstruction of the patient anatomy, the additional neck-stem taper interface is vulnerable to mechanical failure, taper corrosion and release of metal ions. One modular short stem hip implant design was used to pre-clinically evaluate the risk of neck component fracture and metal debris produced at the taper connection in various loading conditions resembling in-vivo situations. Three different fluids were used (Ringer's solution, bovine serum and iron-chloride solution). The usage of bovine calf serum instead of Ringer's solution significantly decreased the endurance limit of the taper connection due to lubrication effects of proteins and other organic components in the contact between stem and neck adapter. The metal ion release increased with increasing chloride concentration and reduced pH-values in the testing fluids. The failures reported for several pre-clinically validated modular hip implant designs are an indicator that an expansion of the current testing procedures according to ISO and ASTM is required to reliably assess the performance of taper junctions prior to clinical use. The developed experimental two-stage testing method, using bovine serum and the adapted iron-chloride solution, is a promising approach to simulate the complex physiological environment in vitro. Highlights: Newly developed biomechanical testing method to simulate the complex physiological environment Expansion of the current testing methods according to ISO and ASTM Two stage biomechanical test procedure Reduction of the endurance limit of the taper connection by using bovine calf serum Simulation of taper corrosion with an adapted FeCl3 -solution